Malvern Tests - ERICE - Vincent, Abhay; Pervier, Marie Laure A.; Pervier, Hugo (Cranfield University, 2023)
This item contains the data from the tests done for characterization of flow using Malvern Particle Analyzer for the ERICE project. Data includes: 1) Labview files (x2) - '.lvm' format (to be read with MS Excel), 2) Excel sheet with data post-processing (x2) - '.xlsx' format (to be read with MS Excel), 3) Test run video files (x2) - '.mkv' files, 4) README txt file (x1) - explaining the headers for the labview data and the instrumentation involved. Test 1 refers to the test run at 60k RPM & Test 2 refers to the test run at 50k RPM
Keywords: ice protection; flow characterization; Air cycle machine; Malvern